Comparing behavioural syndromes across time and ecological conditions in a free-ranging predator. (April 2020) - Dhellemmes, Félicie; Finger, Jean-Sébastien; Laskowski, Kate L.; Guttridge, Tristan L.; Krause, Jens
Abstract : Personality traits (i.e. consistent individual differences in behaviour) often covary, forming behavioural syndromes. Such associations, if driven by an underlying proximate mechanism, could limit the independent evolution of each behaviour. In contrast, a behavioural syndrome may be the result of selection favouring the behavioural correlation under certain ecological circumstances. In this context, investigating the stability and the potential drivers of behavioural syndromes is a fundamental step towards understanding how they might shape the evolution of behaviours. We assessed syndrome stability across time in two subpopulations of free-ranging juvenile lemon sharks, Negaprion brevirostris . We measured two behaviours, exploration in an open field and sociability in a group, over 5 years. We tested whether these behaviours were associated in a behavioural syndrome, how stable this syndrome was and whether its strength was predicted by ecological conditions in this system: predator abundance, juvenile survival, newborn recruitment and total subpopulation size. We found that a behavioural syndrome was only observed in the subpopulation where predatory shark abundance was higher. Across years, newborn recruitment was the main driver for the strength of the syndrome. During years of low recruitment, the subpopulations probably experienced lower competition due to fewer newborns joining the population. In these years, sharks that were more explorative were also less social. These results indicate that the behaviours we tested were plastic and responsive to ecological conditions. Since this could signify that they are only favoured under certain ecological conditions, we argue in this case that the correlation of two behavioural traits is adaptive. Highlights: Behavioural syndromes were inconsistent between subpopulations and years in sharks. The subpopulation with the most predators displayed stronger behavioural syndromes. Newborn recruitment was a main driver of the strength of the syndrome across years.